Unfear : transform your organization to create breakthrough performance and or employee well-being - Bhatnagar, Gaurav; Minukas, Mark (McGraw Hill, 2022)
"Two top experts on high-performing organizations show today's leaders how to reframe their own and their employees' relationship with fear and anxiety to create a learning culture of engaged workers at the top of their game. Fear and uncertainty have been undermining performance and well-being in the workplace for as long as we have had workplaces. Worse, the ever-increasing speed of business, the economic slowdown and volatility we face due to Covid-19, as well as racial tensions and social inequality further exacerbate these emotions. Here's a little-known fact of business: mismanaged fear is responsible for almost all of the dysfunction that most organizations experience. While fear can drive short-term results, it does so at the cost of high employee burnout and turnover. It also undermines long-term business performance. But we can't eradicate it entirely; it is inherent to the human condition. Winning organizations aren't fear-free; they know how to transform that negative energy into opportunities for learning and growth. They create resilient cultures of unfear. In this timely and essential guide, McKinsey alumni Gaurav Bhatnagar and Mark Minukas present a proven approach to workplace anxiety that reduces stress, boosts well-being, and overcomes blocks that get in the way of success. It begins with changing our relationship with fear, and then developing strategies that improve outlook and performance, leading to greater profits, sustainable growth, and personal rewards. It's only possible with a culture of unfear"--